E-Learning implementation in higher education in response to the covid-19 pandemic: a review - Paula Dewanti; Ni Putu Linda Santiari; Kadek Vishnu Vedamurthi (Journal of Science and Education (JSE), 2021)
Through the use of technology, various sectors have shifted as a result of the covid-19 pandemic, including the education system. The educational paradigm evolves by leveraging information technology as a vehicle for scientific growth, and online learning has become a part of our life. Face-to-face sessions in traditional classrooms are transformed into live face-to-face sessions in virtual classrooms. The purpose of this study was to examine the implementation carried out by universities in selected research subject countries using the correspondence method of data collection. Correspondence was performed with contacts at several universities and the Ministry of Education (MOE) in each of the countries that became the focus of this research, including Singapore, Hong Kong, Australia, and Canada, in addition to Indonesia. It was then developed as a best practice based on the use of digital learning as an emergency response to the new corona virus pandemic. The findings indicate that Digital Learning, which involves and effectively uses technology, is an alternative option that is being implemented in these countries as part of the Emergency Plan in the education sector in connection with covid-19.